Bi-objective design of fresh food supply chain networks with reusable and disposable packaging containers. (20th May 2018) - Bortolini, Marco; Galizia, Francesco Gabriele; Mora, Cristina; Botti, Lucia; Rosano, Michele
Abstract: Packaging is crucial in protecting and handling products through the stages of their logistic networks. Actually, both disposable and reusable packaging containers are used. The former ends its life at the last stage of the distribution chain, the latter requires reverse flows to collect, recondition and, then, reuse it. Costs and emissions associated to the two types of packaging containers are different in nature, i.e. raw materials and landfill cost and emissions vs. reverse logistic costs and emissions, so that their choice is not univocal. Furthermore, such choice heavily affects the supply chain network structure and management. This paper addresses this topic aiming at designing a supply chain network including the packaging container best selection, storage/handling node location and flow allocation. An original bi-objective mixed integer linear programming model supports the decisional process. Despite the approach is general, a deep focus is on fresh fruit and vegetable distribution chain because of disposable and reusable packaging containers coexist in practice. The model looks at the cost and environmental impact minimisation over the whole network getting the Pareto frontier and supporting the logistic managers, industrial practitioners and policy makers in the network design and management. A real instance from Emilia-Romagna region, Italy, showcases the model application getting the economic and environmental optima together with best-balance configurations. Results stress the convenience of mixing reusable and disposable packaging containers to reach a global optimum. 47.1% reusable and 52.9% disposable is a possible good balance configuration reducing emissions while containing the cost increase. Graphical abstract: Image 1 Highlights: Integration of product and packaging logistics in the design of effective networks. Focus on fresh fruit and vegetable distribution forward and reverse supply chain. Bi-objective optimisation model to minimise cost and environmental impact. Disposable and reusable packaging containers coexist and are best mixed. Industrial application for Italy reduces disposable containers at acceptable cost.